Pulmonary Embolism following Cessation of Infliximab for Treatment of Miliary Tuberculosis. (28th October 2014) - Lee, Brian; Moosavy, Farid
Abstract : We report a case of a 41-year-old male who presented with tachycardia and swelling of his left arm six weeks after he started antituberculosis treatment and stopped his rheumatoid arthritis infliximab treatment. He was diagnosed with pulmonary embolism by chest CT and initially treated with warfarin, which interacted with his antituberculosis treatment. This presentation of deep vein thrombosis and pulmonary embolism as part of immune reconstitution inflammatory syndrome has not been previously reported for infliximab treated patients.